Avaliação da localização de eletrodos cerebrais profundos implantados para o tratamento de Doença de Parkinson, e o impacto na qualidade de vida. - Renato Rinco Fontoura (2023)
Introduction: Deep brain stimulation (DBS) is a well-stablished treatment for Parkinson's disease (PD). This modality of therapy has direct impacts on the quality of life of patients through the relief of symptoms and mechanisms that are still not completely understood. Objective: To investigate the effects of DBS therapy and the impact on quality of life and establish a correlation between brain electrode placement and a more effective clinical response. Methods: Eleven patients who underwent DBS implantation in the subthalamic nucleus (STN) were evaluated in the preoperative period and 12 months after the procedure using the UPDRS, EQ-5D-3L and PDQ-8 scales in order to compare the intervention results. The coordinates of the implanted brain electrodes were also evaluated, as well as the coordinates of the active treatment poles, in order to establish a correlation with the clinical response. Results: In our series, a reduction of at least 5 points in section III of the UPDRS was found in 72% of the patients, as well as an improvement in the perception of quality of life on the EQ-5D-3L scale, in the same proportion. No correlation was found between the coordinates and the clinical response of the patients. Conclusion: The DBS therapy presents consistent results in the motor improvement of the patients and consequently in their quality of life. In our series, it was not possible to establish more precise coordinates for the improvement of the evaluated patterns.